Sufism In Taufiqurrahman Al Azizy's 3 Wali 1 Bidadari Lelaki Pilihan Abah - Achmad Syuja'i; Akhmad Taufiq; Furoidatul Husniah (Pancaran Pendidikan, 2018)
Sufism are teachings in Islam about the search for truth by doing certain disciplines so as to the knowledge or understanding of God. This understanding of God can be accomplished by practicing through the stage of spiritual ascension, to the contemplation and deeper understanding of God. The concept of the spiritual ascension in the teachings of Sufism is called the maqam, while the meditation on God is called by things. Moreover, in the teachings of Sufism, one who has attained the highest level gains the privilege of God in the form of abilities that can not be done by ordinary people or so-called karomahs (As Sarraj, 1914: 17, Nicholson 1998: 99, Simuh 1997: 49 ). Sufism or tasawwuf teachings are not only taught through the books written by the Sufis, but also contained in literary works such as poetry and stories. Sufism in literature is one way to teach the values of the teachings of Sufism. This is useful for the reader to introspect themselves to be a good human being. The reader can gain a deeper insight and appreciation of the teachings of religion. An example is the reader learns to live and contemplate the Sufi expression in poetry or the sufistic behavior of the story. Such behavior is usually a person's struggle to achieve the highest degree or level in God's eyes. To accomplish that one must cleanse his heart from disgraceful qualities.